Trastuzumab emtansine versus taxane use for previously treated HER2-positive locally advanced or metastatic gastric or gastro-oesophageal junction adenocarcinoma (GATSBY): an international randomised, open-label, adaptive, phase 2/3 study. Issue 5 (May 2017) - Thuss-Patience, Peter C; Shah, Manish A; Ohtsu, Atsushi; Van Cutsem, Eric; Ajani, Jaffer A; Castro, Hugo; Mansoor, Wasat; Chung, Hyun Cheol; Bodoky, Gyorgy; Shitara, Kohei; Phillips, Gail D Lewis; van der Horst, Tina; et al.
Summary: Background: Although trastuzumab plus chemotherapy is the standard of care for first-line treatment of HER2-positive advanced gastric cancer, there is no established therapy in the second-line setting. In GATSBY, we examined the efficacy and tolerability of trastuzumab emtansine in patients previously treated for HER2-positive advanced gastric cancer (unresectable, locally advanced, or metastatic gastric cancer, including adenocarcinoma of the gastro-oesophageal junction). Methods: This is the final analysis from GATSBY, a randomised, open-label, adaptive, phase 2/3 study, done at 107 centres (28 countries worldwide). Eligible patients had HER2-positive advanced gastric cancer and progressed during or after first-line therapy. In stage one of the trial, patients were randomly assigned to treatment groups (2:2:1) to receive intravenous trastuzumab emtansine (3·6 mg/kg every 3 weeks or 2·4 mg/kg weekly) or physician's choice of a taxane (intravenous docetaxel 75 mg/m 2 every 3 weeks or intravenous paclitaxel 80 mg/m 2 weekly). In stage two, patients were randomly assigned to treatment groups (2:1) to receive the independent data monitoring committee (IDMC)-selected dose of trastuzumab emtansine (2·4 mg/kg weekly) or a taxane (same regimen as above). We used permuted block randomisation, stratified by world region, previous HER2-targeted therapy, and previous gastrectomy. The primary endpoint (overall survival) was assessed in the intention-to-treat population. This study is registered withClinicalTrials.gov, numberNCT01641939 . Findings: Between Sept 3, 2012, and Oct 14, 2013, 70 patients were assigned to receive trastuzumab emtansine 3·6 mg/kg every 3 weeks, 75 to receive trastuzumab emtansine 2·4 mg/kg weekly, and 37 to receive a taxane in the stage 1 part of the trial. At the pre-planned interim analysis (Oct 14, 2013), the IDMC selected trastuzumab emtansine 2·4 mg/kg weekly as the dose to proceed to stage 2. By Feb 9, 2015, a further 153 patients had been randomly assigned to receive trastuzumab emtansine 2·4 mg/kg weekly and a further 80 to receive a taxane. At data cutoff, median follow-up was 17·5 months (IQR 12·1–23·0) for the trastuzumab emtansine 2·4 mg/kg weekly group and 15·4 months (9·2–18·1) in the taxane group. Median overall survival was 7·9 months (95% CI 6·7–9·5) with trastuzumab emtansine 2·4 mg/kg weekly and 8·6 months (7·1–11·2) with taxane treatment (hazard ratio 1·15, 95% CI 0·87–1·51, one-sided p=0·86). The trastuzumab emtansine 2·4 mg/kg group had lower incidences of grade 3 or more adverse events (134 [60%] of 224 patients treated with trastuzumab emtansine vs 78 [70%] of 111 patients treated with a taxane), and similar incidences of adverse events leading to death (eight [4%] vs four [4%]), serious adverse events (65 [29%] vs 31 [28%]), and adverse events leading to treatment discontinuation (31 [14%] vs 15 [14%]) than did taxane treatment. The most common grade 3 or more adverse events in the trastuzumab emtansine 2·4 mg/kg weekly group were anaemia (59 [26%]) and thrombocytopenia (25 [11%]) compared with neutropenia (43 [39%]), and anaemia (20 [18%]), in the taxane group. The most common serious adverse events were anaemia (eight [4%]), upper gastrointestinal haemorrhage (eight [4%]), pneumonia (seven [3%]), gastric haemorrhage (six [3%]), and gastrointestinal haemorrhage (five [2%]) in the trastuzumab emtansine 2·4 mg/kg weekly group compared with pneumonia (four [4%]), febrile neutropenia (four [4%]), anaemia (three [3%]), and neutropenia (three [3%]) in the taxane group. Interpretation: Trastuzumab emtansine was not superior to taxane in patients with previously treated, HER2-positive advanced gastric cancer. There is still an unmet need in this patient group and therapeutic options remain limited. Funding: F Hoffmann-La Roche.